Varietal and time dependent differences in juglone and total phenolic contents of the walnut (Juglans regia L.) leaves - Kocaçalışkan, İsmail; Turan, Emel; Ertürk, Ümran; Demir, Yavuz; Terzi, İrfan (Progress in Nutrition, 2020)
From May to October, time dependent differences with two weeks intervals in juglone (5-Hydroxy-1,4-naphthoquinon) and total phenolic content of the leaves of five walnut (Juglans regia L.) culturalvarieties grown in Turkey (cv. Şebin, cv. Yalova-2, cv. Yalova-3, cv. Yalova-4 and cv. 1974/7) were investigated.Juglone and phenolic contents were determined by spectrophotometric methods. Correlations between juglonephenolic content, juglone-climatic factors and phenolic content-climatic factors were also established. In conclusion, there were significant differences between the varieties and the highest values of both juglone andphenolic content were recorded in Yalova-2 cultivar among the varieties. For example, maximum juglone content was determined in Yalova-2 (3,51 mg/g) but minimum in Yalova-4 (2,26 mg/g). Maximum phenolic content was also determined in Yalova-2 (51.8 mg/g), but minimum phenolic level was seen in 1974/7 cultivar (49,3 mg/g), as a mean. On the other hand, both juglone and phenolic content were generally higher from middle of August to middle of September and the lowest levels were seen in May. Further, while a significant positive correlation between juglone and phenolic contents of the leaves was found, there was almost no significant correlation between juglone and climatic factors except a significant negative correlation between phenolic content and wind speed in Yalova-2 cultivar.